The hidden cardiotoxic effect of rofecoxib on rabbit ventricular preparations. (10th June 2022) - Husti, Z; Brenner, G; Bencsik, P; Giricz, Z; Gorbe, A; Varro, A; Ferdinandy, P; Baczko, I
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): National Research, Development and Innovation Office Hungary Introduction: Unexpected ischaemia-induced cardiac adverse events are major contributors to clinical trial discontinuation and drug attrition, and these effects remain undetected by routine preclinical cardiotoxicity assessment. On the other hand, the proarrhythmic effect of drug candidates is studied in healthy cells, tissues, or exclusively in healthy experimental animals. However, a number of experimental and clinical reports demonstrate that the proarrhythmic effects of most drugs are manifested only in pathological conditions. Thus, the aim is to develop a sensitized animal model that can reliably screen for the arrhythmogenic effects of a compound. Here we show that the selective COX- 2 inhibitor rofecoxib, which has been withdrawn over cardiovascular safety concerns, possesses cardiac electrophysiological adverse effects only revealed during ischaemia/reperfusion, a phenomenon we termed "hidden cardiotoxicity". Purpose: Our group has previously reported the hidden cardiotoxic effect of rofecoxib on rat ventricular preparations. Given the significant differences in cardiac electrophysiological properties between rats and humans, the human extrapolation of arrhythmological results obtained from rats is limited, so our aim was to investigate the proarrhythmic effect of rofecoxib in a sensitized rabbit model. Methods: Action potentials were registered from rabbit right ventricular papillary muscles using the conventional microelectrode technique. The following parameters were measured under normoxic and ischaemic conditions in the presence or absence of 10 μM rofecoxib: conduction time, action potential amplitude, action potential duration at 25%, 50%, 75% and 90% repolarization (APD25-90). The effects of rofecoxib upon test ischaemia and reperfusion were investigated. Results: Rofecoxib (10 μM) did not alter electrophysiological parameters in normoxic conditions. However, following 30 minute ischaemia the APD90 was significantly decreased during reperfusion compared to APD90 in the vehicle-treated group: 161.96 ± 19.55 ms vs. 180.04 ± 23.21 ms (p<0.05, n=5), respectively. Following sI/R, a decrease in Vmax and AMPL parameters indicating impulse conduction velocity was also measured in the 10 μM rofecoxib- treated group, but the differences were not statistically significant. Conclusions: Under pathological conditions, rofecoxib may increase the incidence of reperfusion arrhythmias due to the mechanism of delayed afterdepolarization (DAD) and reentrant arrhythmias. Consequently, the sensitized rabbit model detailed above may be suitable for investigating the "hidden cardiotoxic" effect of a drug candidate compound. Significant differences were observed in the effect of rofecoxib on repolarization between the rat and rabbit models. However, due to the well- known electrophysiological differences between the two species, the human relevance of the results obtained in rabbits is more reliable.